Hamiltonian quantization of the non-anomalous generalized Schwinger model - Dutra, Alvaro de Souza [UNESP]; Natividade, C. P. [UNESP] (Springer Nature, 1995)
We quantize a generalized version of the Schwinger model, where the two chiral sectors couples with different strengths to the U(1) gauge field. Starting from a theory which includes a generalized Wess-Zumino term, we obtain the equal time commutation relation for physical fields, both the singular and non-singular cases are considered. The photon propagators are also computed in their gauge dependent and invariant versions. © 1995 Springer-Verlag.